Factors Influencing Third Party Logistics Performance Based On Manufacturer’s Perspective - The Role Of Trust As A Mediator - NADARAJAH, GUNALAN (2004)
This research examines the influence of specific investments, opportunistic behavior, prior satisfaction, third-party logistics (3PL) reputation, reciprocity and communication on outcomes of 3PL performance, and the extent to which trust affects these relationships.